A crítica de poesia hoje e seus dilemas diversos - Pires, Antônio Donizeti (2023)
This study aims to discuss some burning questions in contemporary Brazilian poetry criticism. For this purpose, it is organized in three parts, which comprise: (a) a brief introduction to the problem “Modernity and crisis”, given that such “crisis”, of civilizational basis, still reaches and distinguishes the current thought and production of art and culture; (b) a discussion on the history, methods and main critical currents, as well as their viability nowadays; (c) finally, supported by several critical-theoretical studies, I dwell on the central theme that occupies us with the purpose of starting the discussion, problematization and characterization of the pressing crisis of poetry and contemporary poetry criticism, in Brazil.